Development of a contrast‐enhanced micro computed tomography protocol for the oval squid (Sepioteuthis lessoniana) brain. Issue 11 (14th August 2019) - Sakurai, Yuma; Ikeda, Yuzuru
Abstract: Coleoid cephalopods (squid, cuttlefish, and octopus) have a well‐developed and complex central nervous system. Its absolute size is the largest among invertebrates, and the brain‐to‐body mass ratio is larger than that of fish and reptiles and equivalent to that of birds and mammals. Although a number of histological studies have been conducted on the brains of cephalopods, most of them used a light microscope or an electron microscope, which show the microstructure of the brain, but often cannot image the whole brain instantaneously. Of late, micro computed tomography (CT) has gained popularity for imaging animal brains because it allows for noninvasive three‐dimensional (3D) reconstruction and preprocessing that are not cumbersome. To perform micro‐CT on cephalopod brains, we first tested conditions suitable for preprocessing, paying special attention to staining conditions that would provide high contrast images. Four agents, iodine in 99.5% ethanol, iodine potassium iodide in water (IKI), phosphotungstic acid in 70% ethanol, and nonionic iodinated contrast agent in water, were tested at various concentrations and durations on brain of juvenile oval squid. To evaluate the quality of staining, we calculated the contrast ratio of the two‐dimensional (2D) images and compared 3D segmentation of the best and worst 2D images. We concluded that 3% IKI staining for 7 days was the best combination to enhance the images contrast of the oval squid brain, in which each brain lobe was clearly detected and 3D segmentation of the whole brain was possible. The wider applicability of this preprocessing method for micro‐CT of the brains of other cephalopods is discussed. Abstract : Protocol for microcomputed tomography on brain of juvenile oval squid was examined. Visibility of scan image for brain depended on the concentration of contrast agents. 3% Iodine potassium iodide in water (stained ≥7 days) was the best contrast‐enhanced agent.